Consciência e vontade geral: da natureza ao Estado - Tamíris Moreira Simão (2017)
In Rousseaus work, when man isnt able to harmonize his nature and social acquisitions, there is a rupture and conflict. To solve this problem, Rousseau thinks in some alternatives and one of them is the establishment of a social order that is capable to harmonize nature and society, adapting the natural qualities, and preserving one of the most important human qualities: the liberty. To ensure liberty, which Rousseau believes is necessary for humans to maintain their humanity, the philosopher uses two central conceptions: sovereignty and general will. Shortly, we can say that when citizens obey the laws, that are expressions of the general will, they are obeying their own will and, therefore, they are free. But how are citizens able to recognize, among their wills, the general will? This is an important problem in Rousseaus political theory, and this is what were trying to discover in our research. With the objective of figuring this problem out, we started our work studying the human nature and the conflict that happens with men. For this, we studied specially the Discourse on the origin and the foundations of inequality among men; Emile or on education; and Julie or the new Heloise. After we understand human nature and this conflict, we try to realize how the natural qualities in humans remain in society, and how they change in social men. When we understand that, we notice that part of the problems solution is in how these qualities act in social order. The self-love is the primordial sentiment that conserves mens lives in the state of nature, and at the civil state it becomes love for society; when a man thinks about his own preservation and well-being, hes able to recognize the general will. The self-love, however, is not the only necessary thing to make this happen, and we show in our paperwork that it depends also on reason and conscience. Furthermore, the love of society can only exist when the society can actually guarantee the citizens rights. To show that, we studied The Social Contract, Discourse on political economy and Considerations on government of Poland, and we noticed that the State has to deserve to be loved and to provide institutions that are able to make the citizens relate to each other and to State, and to denature men, making their lives more harmonic. Therefore, in our research we try to show that the process to recognize the general will depends on self-love, conscience, reason, and social institutions that can strengthen the connection between the citizens and the State.